Sodium-Glucose Co-Transporter-2 Inhibitors in Non-Diabetic Adults With Overweight or Obesity: A Systematic Review and Meta-Analysis - Zheng, Hanrui; Liu, Min; Li, Sheyu; Shi, Qingyang; Zhang, Shengzhao; Zhou, Yiling; Su, Na (Frontiers in Endocrinology, 2021)
Background: Sodium-glucose-cotransporter-2 (SGLT2) inhibitors have proven to be effective in improving glycemic control and lowering body weight in patients with type 2 diabetes mellitus. However, the efficacy and safety on weight loss in adults with overweight or obesity but not diabetes remain unclear. In this article, we aimed to identify the efficacy and safety of SGLT2 inhibitors in adults with overweight or obesity but not diabetes in randomized controlled studies (RCTs). Methods: We searched for RCTs concerning SGLT2 inhibitors in adults with overweight or obesity but not diabetes in Medline (Ovid SP), Embase (Ovid SP), Cochrane Central Register of Controlled Trials (Ovid SP), and ClinicalTrials.gov up to February 2021. The primary outcomes were changes in body weight and body mass index (BMI). Trial sequential analysis (TSA) was used to test the reliability of the primary outcomes. We analyzed the data using Review Manager 5.3 and pooled data to calculate the mean differences (MDs) or the relative risk (RR). We assessed the evidence quality of evidence of outcomes according to GRADE. Results: Six randomized controlled trials involving 872 individuals were included in the meta-analysis. Compared to the placebo group, the SGLT2 inhibitors group had statistically significant reductions in absolute changes in body weight (MD: -1.42 kg, 95% CI: -1.70 to -1.14; P<0.00001) and BMI (MD: -0.47 kg/m2, 95% CI: -0.63 to -0.31; P<0.00001) in SGLT2 inhibitors group, as indicated by TSA. However, no significant benefits were observed in the SGLT2 inhibitors group in terms of waist circumference (MD: -1.34 cm, 95%CI: -2.75 to 0.07; Z=1.86, P=0.06) compared with the placebo group. The GRADE profiles indicated very low-quality evidence for body weight change and low-quality evidence for BMI change. SGLT2 inhibitors were generally safe and well tolerated. Conclusion: SGLT2 inhibitors could significantly reduce body weight in adults with overweight or obesity but not diabetes compared with placebo. Apart from higher rates of genital mycotic infections (especially in women), SGLT2 inhibitors were generally well tolerated. Further studies are warranted to confirm the efficacy and safety of SGLT2 inhibitors in adults with overweight or obesity but not diabetes for long-term weight management.